Comparative Assessment and Future Prediction Using CMIP6 and CMIP5 for Annual Precipitation and Extreme Precipitation Simulation - Li, Jingjing; Huo, Ran; Chen, Hua; Zhao, Ying; Zhao, Tianhui (Frontiers in Earth Science, 2021)
This study assesses the improvement of the latest Coupled Model Intercomparison Project Phase 6 (CMIP6) over CMIP5 for precipitation simulation. Precipitation simulations under different future climate scenarios are also compared in this work. The results show that: (1) CMIP6 is slightly better than CMIP5 in simulating total precipitation (PRCPTOT) and maximum consecutive dry days (CDD) but is slightly worse than CMIP5 in simulating very wet days (R95pTOT). (2) Comparing the trend test results of CMIP5 and CMIP6 in the future, the differences in PRCPTOT are mainly found in South America. The differences between the R95pTOT trends are small and mainly noticeable in Africa, and the differences in CDD are mainly reflected in Northeast Asia, around the Mediterranean, and the Sahara Desert. (3) Analyzing the changing rates in the 21 regions in the near-future and far-future periods over the historical period, it can be found that the simulation of PRCPTOT changing rates in CMIP6 is less than that of CMIP5 in Northeast Asia. The simulation of CDD changing rates in CMIP6 is less than that in CMIP5 in South America, southern North America, southern Africa, and Australia. The results provide support for making plans for climate change.